2001
DOI: 10.1007/978-1-4613-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Polarization, Alignment, and Orientation in Atomic Collisions

Abstract: The Springer Series on Atomic, Optical, and Plasma Physics covers in a comprehensive manner theory and experiment in the entire field of atoms and molecules and their interaction with electromagnetic radiation. Books in the series provide a rich source of new ideas and techniques with wide applications in fields such as chemistry, materials science, astrophysics, surface science, plasma technology, advanced optics, aeronomy, and engineering. Laser physics is a particular connecting theme that has provided much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 0 publications
3
109
0
Order By: Relevance
“…On the other hand, if identically prepared states are produced, a coherent mixture of the magnetic sublevels of the excited state is observed. For example, an excited 1 P o state can be described as |ψ 1 P = a +1 |11 + a 0 |10 + a −1 |1 − 1 (8.4) where the a M are the excitation amplitudes for the sublevels |LM with magnetic quantum number M. Theoretical analyses of coherent excitation can be found in Blum (1996), Andersen, Gallagher and Hertel (1988), and Andersen and Bartschat (2001).…”
Section: Angular and Polarization Correlationsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, if identically prepared states are produced, a coherent mixture of the magnetic sublevels of the excited state is observed. For example, an excited 1 P o state can be described as |ψ 1 P = a +1 |11 + a 0 |10 + a −1 |1 − 1 (8.4) where the a M are the excitation amplitudes for the sublevels |LM with magnetic quantum number M. Theoretical analyses of coherent excitation can be found in Blum (1996), Andersen, Gallagher and Hertel (1988), and Andersen and Bartschat (2001).…”
Section: Angular and Polarization Correlationsmentioning
confidence: 99%
“…Closed squares, Yalim, Cvejanovic and Crowe (1997); closed and open circles, Williams and Mikosza (2006); closed triangles, Gradziel and O'Neill (2004); open triangles, O'Neill et al (1998);open squares, Nic Chormaic, Chwirot and Slevin (1993); open diamonds, Williams (1986); full line, the PECS theory of Bartlett et al (2005). Adapted from Williams and Mikosza (2006 More detailed reviews of angular and polarization correlation and superelastic scattering studies were given by Andersen, Gallagher and Hertel (1988) Andersen et al (1997), and Andersen and Bartschat (2001).…”
Section: Angular and Polarization Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The atomic collision processes [1][2][3][4][5][6][7][8][9][10][11] such as the elastic collision, electron-impact excitation and ionization, and electron capture have received considerable interests in astrophysics, atomic physics, and plasma physics since the collision processes provide useful information on the collision mechanisms as well as the surrounding physical environments including the collision system. It is shown that the time-development of the atomic collision process has the physical characteristics of the energy dependence since the phase shift contains the physical information of the collision process [1,4].…”
mentioning
confidence: 99%